Privatskogsägarens nettoinkomst vid avverkning under perioden 1952-2008 - Pettersson, Marcus (2011)
During the period 1952-2008, real prices of wood before taxes and charges declined. However, the actual net income has not changed by the same percentage as the price list, because taxation, driving costs and the ability to make deductions has changed. This report considers the inflation by using the Swedish consumer price index. Net income refers to the remaining income when relevant costs, taxes and fees have been paid. The purpose of this study was to examine how the private forest owner's real net income has evolved over the period 1952-2008 for three categories of forest owners. These three categories are 1. A forest owner who only makes his living on income from his or her forest property and who personally undertakes the forest management activities such as harvesting, planting etc. 2. A forest owner who has an "average” income from other services 3. A forest owner who has a "higher than average" income from other services Wood prices have, each year, been reduced by costs of harvesting and replanting etc, income taxes and social contributions that forest owners had to pay. In addition to these taxes, forest owners were also burdened with a forest management fee, which also is included in the calculations. The results show that the net income of the forest owner in category 1 declined by about 70% from 1952 to the end of the 1970s. After that point in time, it was more or less constant. The real net incomes for categories 2 and 3 are currently about 60 % lower than in 1952. If we investigate the period after 1956, 1995 is the year that yielded the highest net income for the categories 2 and 3. The actual cost of the forest management fee was highest for the forest owner in category 1, and lowest for the forest owner in category 3. The option to tax a part of the forest revenue as capital income favored the highly paid forest owner (category 3) the most. If forest revenues are compared to salaries of industrial workers, the development of the timber price looks even worse. In 1952, the gross income of a forest owner in category 1, when harvesting 450 m3fpb, was 3,5 times higher than the gross income of an industrial worker. In 2008, the gross income of the industrial worker was approximately 3 times higher than that of a forest owner in category 1, when harvesting 450 m3fpb. Forest revenues have thus increasingly come to be regarded as a secondary source of income compared to regular work.